The The Impact of Entrepreneurial Orientation and Social Capital on Culinary Business Performance in Surabaya with the Knowledge Creation Process as a Mediating Variable - Dewantoro, Albertus Daru; Christiananta, Budiman; Ellitan, Lena (Program MM Universitas Surabaya, 2024)
Purpose: This study examines factors influencing culinary business performance in Surabaya, focusing on the relationship between entrepreneurial orientation, social capital, and business performance, with knowledge creation as a mediating variable. Method: Data were collected from 345 micro, small, and medium-scale culinary entrepreneurs in Surabaya. The analysis used Structural Equation Modeling (SEM) with 2nd order Confirmatory Factor Analysis (CFA) via AMOS 22 software Result: Entrepreneurial orientation and social capital significantly affect knowledge creation and business performance. The SECI-based knowledge creation process positively impacts business performance and partially mediates the relationship between entrepreneurial orientation and business performance.